The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s40708-022-00179-z
|View full text |Cite
|
Sign up to set email alerts
|

Error-related brain state analysis using electroencephalography in conjunction with functional near-infrared spectroscopy during a complex surgical motor task

Abstract: Error-based learning is one of the basic skill acquisition mechanisms that can be modeled as a perception–action system and investigated based on brain–behavior analysis during skill training. Here, the error-related chain of mental processes is postulated to depend on the skill level leading to a difference in the contextual switching of the brain states on error commission. Therefore, the objective of this paper was to compare error-related brain states, measured with multi-modal portable brain imaging, betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(52 citation statements)
references
References 103 publications
1
34
0
Order By: Relevance
“…In our prior work (Walia et al, 2022a), we have shown contextual switching of the brain state during laparoscopic suturing with intracorporeal knot tying task-errors that can be related to error perception and corrective action (Benozzo et al, 2021). In the current study, we performed tDCS of the left VLPFC to facilitate subjective task-error awareness (Wessel, 2012) by activating the ventral attention system (Vossel et al, 2014).…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…In our prior work (Walia et al, 2022a), we have shown contextual switching of the brain state during laparoscopic suturing with intracorporeal knot tying task-errors that can be related to error perception and corrective action (Benozzo et al, 2021). In the current study, we performed tDCS of the left VLPFC to facilitate subjective task-error awareness (Wessel, 2012) by activating the ventral attention system (Vossel et al, 2014).…”
Section: Introductionmentioning
confidence: 85%
“…The ventral stream (Kamat et al, 2022a), which senses the feedback ( external monitoring ) of the environment in the primary sensory cortex, flows to the sensory association cortex, and then to the posterior association cortex (such as the supramarginal gyrus), leading to the perception of conscious errors in the ventrolateral prefrontal cortex (VLPFC). Here, controlled goaldirected attention may be facilitated with tDCS of the dorsolateral PFC (Ashcroft et al, 2020) while (unexpected) error stimulus-driven attention may need tDCS of the VLPFC (Walia et al, 2022a), (Walia et al, 2021a) indeed, they have dissociable brain connectivity (Seeley et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations